THE ROLE OF THE HEAD OF MADRASAH'S POLICY IN IMPROVING TEACHER PROFESSIONALISM - Ahmat Nurulloh; Andika Aprilianto; Akhmad Sirojuddin; Muhammad Anas Maarif (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This article aims to find out about the role of madrasa principals' policies in improving the professionalism of teachers at Madrasah Tsanawiyah (MTs) Unggulan Hikmatul Amanah. The research method used is descriptive-qualitative by using data collection techniques in the form of observation, documentation and discourse. The subjects of this study were the principal of the madrasa, teacher training staff and teachers at MTs Unggulan Hikmatul Amanah. The results of this study indicate that the policies of the head of the madrasa at MTs Unggulan Hikmatul Amanah are quite good, in this case the role of the principal's policies in order to increase teacher professionalism is very dominant. The principal of madrasa implements the policy by holding monthly meetings; giving assignments; holding training, seminars, workshops; provide rewards/allowances to teachers who excel and sanctions for teachers who violate policies in madrasah. Teacher professionalism is well improved, seen in: active discipline in learning; skill development, and being able to master the material in learning.